2013
DOI: 10.1177/0885066613511048
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Hypoglycemia Treatment Protocol on Glycemic Variability in Critically Ill Patients

Abstract: Implementation of the hypoglycemia treatment protocol described led to a reduction in glucose variability, while still providing a safe and effective way to manage hypoglycemia in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Patient factors such as age, sex, use of D10% after initiation of D40%, time to recheck blood glucose, use of insulin, insulin secretagogue, other OAD, CKD, liver disease, and status of recurrent hypoglycaemia were found to have minimal impact to blood sugar response. This finding was in an agreement with previous study by Arnold et al 15 Non-significant differences in post-correction blood sugar response from administration of D40% iv bolus and infusion in this study can be caused by the small number of samples. The preference for using D40% concentrated solution for the management of hypoglycaemia at this time is by iv infusion for 15 minutes until proven through further research.…”
Section: Discussionsupporting
confidence: 94%
“…Patient factors such as age, sex, use of D10% after initiation of D40%, time to recheck blood glucose, use of insulin, insulin secretagogue, other OAD, CKD, liver disease, and status of recurrent hypoglycaemia were found to have minimal impact to blood sugar response. This finding was in an agreement with previous study by Arnold et al 15 Non-significant differences in post-correction blood sugar response from administration of D40% iv bolus and infusion in this study can be caused by the small number of samples. The preference for using D40% concentrated solution for the management of hypoglycaemia at this time is by iv infusion for 15 minutes until proven through further research.…”
Section: Discussionsupporting
confidence: 94%
“…[14][15][16] All meta-analyses and systematic reviews conclude that TGC does not reduce mortality, but increases the incidence of hypoglycemia strongly. 17,18 Insulin-induced hypoglycemia may thus be the culprit in mitigating the benefits of TGC.…”
Section: Blood Glucose Control: the Clinical Trialsmentioning
confidence: 99%
“…38 While the concept of iatrogenic GV-a product of overcorrection of BG levels upon administration of dextrose to correct episodes of hypoglycemia-has been brought up in the past, newer protocols have been described to minimize GV while allowing for appropriate management of hypoglycemia in critical illness. 39 Mechanistically, in vitro studies have linked marked fluctuations in BG level with increase in oxidative stress and downstream endothelial dysfunction and cellular apoptosis. 40,41 Additional in vivo studies have also shown that glucose variability exerts a stronger influence as a cause of oxidative stress compared with sustained hyperglycemia.…”
Section: Glycemic Variabilitymentioning
confidence: 99%